Black Hole Attack Detection Using HlA with Optimized Link State Routing Protocol In Wanet (International Journal of Engineering and Computer Science, 2016)
A wireless ad-hoc network also known as autonomous Basic Service Set which is a computer network in which the communication links are wireless. In ad-hoc network each node can forward data for other nodes and so the determination of which nodes forward data is made dynamically depended on the network connectivity. There are two kinds of sources that providing packet losses are link failure and dropping of packets by adversary activities in multi-hop wireless ad hoc network. While observing a continuous packet losses in the network for determining whether the packet drops are occurred by link errors or by the joined effect of link errors and malicious drop. To improve the detection accuracy of adversary an enhanced Optimized Link State Routing Protocol (OLSR) is used to correctly broadcast the routing protocol control traffic on behalf of other nodes. Homomorphic Linear Authenticator (HLA) based public auditing scheme allows the detector to calculate the truthfulness of the packet loss information informed by nodes. This algorithm is privacy preserving and find the optimal path during transmission.